EFFECT OF ONLINE LEARNING, EMOTIONAL INTELLIGENCE, INTELLECTUAL INTELLIGENCE AND SOCIAL INTELLIGENCE ON STUDENT PERFORMANCE IN BATAM CITY IN TIME OF COVID-19 - Rona Tanjung; Sri Mulyati; Eka Kurnia Saputra; Ferry Muliadi Manalu; Magneta Hisyam (Bajang Institute, 2022)
This study aims to analyze the effect of Online Learning, emotional intelligence, intellectual intelligence, sosial intelligence partially and simultaneously on student performance. The type of data used in this study is quantative data with data techniques using a questionnaire. The population in this study is management students of Riau Kepulauan University. The sampling using the Slovin formula and getting a sample of 60 students. The results of this study indicate that: 1. Online learning affects student performance, 2. Emotional intelligence affects student performance, 3. Intellectual intelligence does not affect student performance, 4. Social intelligence affects student performance. as evidenced by the value of fcount 30.447 > ftabel 2.05 and a significance value of 0.000 <0.05.